Double-Framed Soft Hypervector Spaces - G. Muhiuddin; Abdullah M. Al-Roqi (The Scientific World Journal)
The notions of double-framed soft subfields, double-framed soft algebras over double-framed soft subfields, and double-framed soft hypervector spaces are introduced, and their properties and characterizations are considered.